Youth social behaviour and network therapy (Y-SBNT): adaptation of a family and social network intervention for young people who misuse alcohol and drugs – a randomised controlled feasibility trial - Judith Watson (Health Technology Assessment, 2017)
Background: Family interventions appear to be effective at treating young people’s substance misuse. However, implementation of family approaches in UK services is low. This study aimed to demonstrate the feasibility of recruiting young people to an intervention based on an adaptation of adult social behaviour and network therapy. It also sought to involve young people with experience of using substance misuse services in the research process. Objectives: To demonstrate the feasibility of recruiting young people to family and social network therapy and to explore ways in which young people with experience of using substance misuse services could be involved in a study of this nature. Design: A pragmatic, two-armed, randomised controlled open feasibility trial. Setting: Two UK-based treatment services for young people with substance use problems, with recruitment taking place from May to November 2014. Participants: Young people aged 12–18 years, newly referred and accepted for structured interventions for drug and/or alcohol problems. Interventions: A remote, web-based computer randomisation system allocated young people to adapted youth social behaviour and network therapy (Y-SBNT) or treatment as usual (TAU). Y-SBNT participants were intended to receive up to six 50-minute sessions over a maximum of 12 weeks. TAU participants continued to receive usual care delivered by their service. Main outcome measures: Feasibility was measured by recruitment rates, retention in treatment and follow-up completion rates. The main clinical outcome was the proportion of days on which the main problem substance was used in the preceding 90-day period as captured by the Timeline Follow-Back interview at 3 and 12 months. Results: In total, 53 young people were randomised (Y-SBNT, n = 26; TAU, n = 27) against a target of 60 (88.3%). Forty-two young people attended at least one treatment session [Y-SBNT 22/26 (84.6%); TAU 20/27 (74.1%)]; follow-up rates were 77.4% at month 3 and 73.6% at month 12. Data for nine young people were missing at both months 3 and 12, so the main clinical outcome analysis was based on 24 young people (92.3%) in the Y-SBNT group and 20 young people (74.1%) in the TAU group. At month 12, the average proportion of days that the main problem substance was used in the preceding 90 days was higher in the Y-SBNT group than in the TAU group (0.54 vs. 0.41; adjusted mean difference 0.13, 95% confidence interval –0.12 to 0.39; p = 0.30). No adverse events were reported. Seventeen young people with experience of substance misuse services were actively involved throughout the study. They informed key elements of the intervention and research process, ensuring that the intervention was acceptable and relevant to our target groups; contributing to the design of key trial documents, ideas for a new model of public involvement and this report. Two parents were also involved. Conclusions: The adapted intervention could be delivered in young people’s services, and qualitative interviews found that Y-SBNT was acceptable to young people, family members and staff. Engagement of family and network members proved difficult within the intervention and research aspects. The study proved the feasibility of this work in routine services but outcome measurement based on narrow substance use variables may be limited and may fail to capture other important changes in wider areas of functioning for young people. Validation of the EuroQol-5 Dimensions for young people aged 12–18 years should be considered and flexible models for involvement of young people in research are required to achieve inclusive representation throughout all aspects of the research process. Although recommendation of a full trial of the Y-SBNT intervention compared with TAU is not supported, this study can inform future intervention development and UK research within routine addiction services. Trial registration: Current Controlled Trials ISRCTN93446265. Funding: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 21, No. 15. See the NIHR Journals Library website for further project information.